Ensino de leitura de sentenças: contribuições da análise do comportamento - HAYDU, Verônica Bender (2016)
The stimulus equivalence paradigm has been used infrequently in studies of sentence reading. Therefore, the present study evaluated the effect of a procedure involving teaching and testing conditional relations followed by the chaining of words upon sentence reading with comprehension and reading generalization. Eight students, 7 to 9 years old, participated in the study. The procedure included a pre- and post-test, three teaching phases and reading with comprehension tests, a connectivity test, and a sentence construction test. Words and sentences reading improved from pre- to post-test in all cases, showing that the procedure was effective in teaching sentence reading with comprehension.